Attitudes toward new organizational technology: network proximity as a mechanism for social information processing. - Rice, Ronald E.; Aydin, Carolyn (Administrative Science Quarterly, 1991)
A study explicated and tested 3 network-based mechanisms whereby individuals' attitudes toward an integrated health information system may be influenced by the attitudes of relationally, positionally, and spatially proximate sources of social information. The focus was on the implementation of an integrated health information system at a university student health service (SHS). Questionnaires completed by 62-96 SHS department members were analyzed. The results show that estimates of the attitudes of generalized others are not convincingly associated with specified others' actual attitudes. Generally, specific others' actual attitudes have just a small effect on one's attitude. Social information operates positively through communication and work-unit mechanisms and negatively through the mean attitude of one's structurally equivalent position but not through overall organizational or spatial proximity.